The Protocol for Active Movement Extent Discrimination Assessment (AMEDA) is Reliable When Shortened From 50 to 25 Stimuli to Reduce Testing Fatigue. - Waddington, Gordon; Witchalls, Jeremy (Perceptual & Motor Skills, 2025)
Active movement extent discrimination assessment (AMEDA) is a psychophysical task that evaluates proprioception and tactile acuity of the lower limbs, and it is a method of determining sensorimotor ability. Sensorimotor ability is the ability to judge small differences in movement tasks through the process of receiving sensory messages (sensory input) and producing a response (motor output). Participant attention lapses in prior psychophysical studies have been implicated as a cause for increased measurement variance thresholds in these types of assessments. Since minimizing the time needed for the AMEDA may help to reduce attention lapses, we compared the reliability of the 50-repetition AMEDA protocol (Group 1) with that of a 25-repetition protocol (Group 2). We assessed the split half reliability of these two approaches, using the Spearman-Brown Adjusted Pearson correlation (r). For each method, we calculated Bland-Altman Plots and Intra Class Correlation Coefficients to compare the reliability of the two data sets and determine the 95% confidence intervals. Split-half test re-test Spearman-Brown Adjusted Pearson r (r) was Group 1 r = 0.83 and Group 2 r = 0.85. The Bland-Altman Plots indicated only a small degree of bias from the zero-difference line, with 95% of the difference points lying within the limits of agreement. For Group 1, the intraclass correlation coefficient (ICC) two-way, agreement was 0.83 (95% CI 0.54–0.93) and for Group 2, the ICC, two-way, agreement, was 0.85 (95% CI 0.66–0.93). The MDC90 for Group 1 was 0.082 AUC units and for Group 2, it was 0.086 AUC units. The combined data for Group 1 plus Group 2 Bland-Altman Plot indicated only a small degree of bias from the zero-difference line, with 95% of the difference points lying within the limits of agreement. The MDC90 for the combined groups was 0.08 AUC units. The multiple methods from previous research assessing test re-test reliability that we applied to our two data sets indicate that the 25-response AMEDA was a reliable system for evaluating sensorimotor function in the lower limbs and may be an alternative for the more traditional 50-response protocol in which lapses in participant attention from fatigue or other biases may be a concern. There are also practical advantages in time restricted athletic screenings to a shorter administration of this assessment.